2010
DOI: 10.1158/0008-5472.can-10-0300
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Receptor for B-Cell–Activating Factor Is Expressed on Human Acute Lymphoblastic Leukemias

Abstract: B-lineage acute lymphoblastic leukemia (ALL) arises by transformation of a progenitor (pre-B) cell. Cure rates in adults remain low and treatment is complicated by support provided by the microenvironment to the leukemic cells, indicating an urgent need to better understand the factors that promote their survival.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 47 publications
8
76
1
3
Order By: Relevance
“…[11][12][13][14] Although a decrease in CLL patients' circulating BAFF levels damages the hypothesis that BAFF plays a role in tumorigenesis, it is consistent with the malignant cell survival and dampen normal humoral immunity through BAFF-binding. Our studies reported here using precursor B-ALL-derived cell lines support the recently published finding that precursor B cell cancers aberrantly express BAFF-R. 19 These cell lines enabled us to study the mechanisms of expression in a straight-forward way with abundant, manipulatable material.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…[11][12][13][14] Although a decrease in CLL patients' circulating BAFF levels damages the hypothesis that BAFF plays a role in tumorigenesis, it is consistent with the malignant cell survival and dampen normal humoral immunity through BAFF-binding. Our studies reported here using precursor B-ALL-derived cell lines support the recently published finding that precursor B cell cancers aberrantly express BAFF-R. 19 These cell lines enabled us to study the mechanisms of expression in a straight-forward way with abundant, manipulatable material.…”
Section: Introductionsupporting
confidence: 86%
“…1A) are consistent with a recent report demonstrating the presence of BAFF-R on the surface of primary precursor B-ALL cells. 19 We were encouraged to pursue this observation as reflective of a striking and unexpected phenomenon common to B lineage ALL malignancies. This aberrant BAFF-R expression may indeed fuel the growth of these cancers and even play a role in their tumorigenesis, as their normal counterparts entirely lack expression of this anti-apoptotic and costimulatory cytokine receptor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, a recent research [9] presented evidence that the BAFF-R is universally expressed on Blineage acute lymphoblastic leukemia (ALL) cells which develop by transformation of normal B-cell progenitors. Other studies have demonstrated that the fusion protein of BAFF and gelonin, a plant toxin, had the killing effects against BAFF-R (+) B lymphoma cells [10,11] .…”
Section: Discussionmentioning
confidence: 99%